Hydrostatic high pressure applied to food sterilization, III. Application to spices and spice mixtures - Butz, Peter; Heinisch, Oliver; Tauscher, Bernhard (High pressure research, 1994)
The response of suspensions of spices and spice mixtures in water to high pressure treatment was investigated. Inactivation of the microbial load-mainly aerobic and unaerobic spore formers-was strongly dependent on water activity and temperature. Samples were completely decontaminated after three pressure cycles (30 min at 80 MPa followed by 30 min at 350 MPa) at 70 °C at a minimum water activity of 0.91. Pressure treated samples were examined for sensory and chemical changes. No significant changes in odour and appearance were recognized by a trained sensory panel, nor were changes in the volatile compounds of the samples detected by static headspace gaschromatography.
Online veröffentlicht: 19. Aug 2006
Gesehen am 15.01.2026